Did mangrove communities exist in the Late Cretaceous of the Kristianstad Basin, Sweden? - McLoughlin, S.; Haig, D.; Siversson, Ulf; Einarsson, E. (Elsevier BV, 2018)
Previous inferences of oyster-dominated communities occupying mangrove-like depositional settings in the Kristianstad Basin, Sweden, during the late early Campanian are reassessed. A significant percentage of oysters (Acutostrea incurva) from the Belemnellocamax mammillatus zone in Bed 3 at Åsen bear indentations on their left valves indicating attachment to plant axes. Many of these axes bear morphological features characteristic of the distal subaerial portions of woody plant branches and appear to have been rafted into the marine environment rather than representing in situ mangrove stems and roots. Foraminiferal assemblages recovered from sediment within the oyster body cavities differ from modern mangrove-community associations by the absence of siliceous agglutinated Foraminifera, the presence of diverse and relatively abundant Lagenida, relatively common triserial Buliminida, and a notable percentage of planktonic taxa. Chondrichthyan teeth assemblages from the same beds are similarly incompatible with the interpretation of a mangrove depositional environment based on comparisons with the distribution of related extant taxa. Apart from oyster shells and belemnite rostra, these beds are notably depauperate in diversity and abundance of macroinvertebrate remains compared with coeval carbonate shoal and rocky shoreline assemblages from the same basin. The collective palaeontological and sedimentological evidence favours an inner neritic sandy-substrate setting, but not nearshore or mangrove-like depositional environment for the oyster-rich Bed 3 at Åsen. The absence of mangrove-like assemblages at Åsen is consistent with the development of modern mangrove ecosystems much later (during the Maastrichtian and Cenozoic) based on the global palynological record.